Segmented stochastic convergence across the G-7 countries - Roberto Cellini; Antonello Scorcu (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1998)
This paper analyzes the stochastic convergence in per capita income levels among the current G-7 over the period 1900-89. We show that, in the presence of possible structural breaks, the strong condition of stationary pair-wise differences between per capita GDP holds in many more cases than generally supposed. However, it occurs more frequently in the first part of the time sample than in the second one.
Keywords: 330